Association of short chain fatty acid profile and nutritional intake of malnourished children in Indonesia - Pratiwi, Rina; Rahmadi, Farid Agung; Anam, Moh Syarofil; Pratiwi, Juwita; Mexitalia, Maria (Progress in Nutrition, 2025)
Background and aim: Stunting and wasting prevalence in Indonesia are considered really high (31% and 10.2% respectively), which have been major global issue. On the gastrointestinal system of malnourished children, there are gut microbiota alterations. Dysbiosis and functional capacity change affects short-chain fatty acid (SCFA) production, causing inefficient nutrition uptake. This study aimed to analyze the correlation of SCFA profile and nutritional intake of malnourished children, including the association of risk factors in malnourished children.Methods: Fourty children (25 males, 15 females) with stunted and/or wasted according to World Health Organization (WHO) growth chart were included in this study. Anthropometric measurements and physical examination were done by pediatrician. Questionnare about child’s gestational age, exclusive breastfeeding status, congenital disease, antibiotic consumption, and dietary intake using 3-days food recall were filled by parents/ caregivers. Fecal and SCFA analysis was done by GC-MS at laboratory in Semarang, Indonesia. Intergroup differences and association were compared using Spearman and Mann-Whitney test.Results: Children with double malnutrition have different SCFA profile than children with single malnutrition, especially in acetic and propionic acid. There is a correlation between fibre intake and propionic acid in malnourished children (p=0.037). Antibiotic usage and malabsorption contribute significantly in SCFA profile (p=0.033, 0.016, 0.042). Fibre and leukocytes count in feces are correlated with SCFA profile (p=0.013, 0.024).Conclusions: There is correlation between fibre intake and propionic acid levels in malnourished children. Antibiotic usage is associated with propionic and valeric acid levels, while malabsorption is associated with butyric acid levels.